Analisis SWOT Pembelajaran Pendidikan Agama Islam pada Kurikulum Merdeka di Sekolah Penggerak - Alfarizi, Lutfi; Umam, Khotibul; Fathiyaturrahmah, Fathiyaturrahmah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to identify strengths and weaknesses, as well as opportunities and threats in PAI learning at SMP 11 Ma'arif Bangsalsari Jember. Thus, the school can find appropriate and measurable steps to make decisions. In this study, a qualitative research approach was used with the SWOT matrix analysis method. The data used were taken from respondents who had filled out a questionnaire prepared by the researcher. The data were then grouped based on SWOT aspects and analyzed using the SWOT matrix approach. The results of this study show that in the internal aspect, the independent curriculum gives freedom to PAI teachers to develop a learning process that can be adapted to the needs of students. However, the weakness found is the limited resources and facilities in the institution that greatly affect the learning process. In the external aspect, PAI learning has a wider opportunity to develop Islamic religious values according to individual abilities. However, the threat is that differences in interpretation between teachers can cause conflicts that lead to disunity, which can reduce the intensity and quality of PAI learning. Based on these internal and external aspects, there are several steps that PAI teachers should take. First, teachers need to innovate in PAI learning optimally. Second, teachers need to expand relationships with the community and clerics to improve social competence. Third, PAI teachers must have enthusiasm and continue to improve professionalism in carrying out academic duties. Fourth, teachers need to increase support from the education office and school leadership in facilitating PAI learning activities. Fifth, PAI teachers need to improve their ability and cohesiveness in understanding the implementation of the independent curriculum. Sixth, teachers need to improve quality in the realm of professionalism and understanding of the concept of religious moderation. Seventh, teachers need to be equipped with skills in developing interesting and effective PAI learning for students. Eighth, teachers need to communicate with school leaders and the education office to provide and prepare supporting facilities in PAI learning.